Konseling Kelompok Cognitive Behavior Therapy untuk Meningkatkan Manajemen Emosi - Agus Rizal; Putri Luluk Amiaty; Wisnu Kurniawan (Bulletin of Counseling and Psychotherapy, 2026)
Emotion management is essential for addressing the academic, social, and personal challenges faced by students. The ability to regulate emotions affects self-control, the formation of social relationships, and adaptation to environmental demands. Group counseling based on a cognitive-behavioral approach serves as an intervention aimed at transforming irrational thought patterns and maladaptive behaviors into more constructive alternatives. This study utilized a quantitative, one-group pre-test - post-test pre-experimental design. The sample consisted of seven students, purposively selected from two 11th-grade classes at Mojoagung State Senior High School, who met the criteria for low emotional management. The emotional management questionnaire, developed according to Thompson's theory, demonstrated both validity and reliability. Of the 52 initial items, 33 were found to be valid (r > 0.367) and reliable (Cronbach's Alpha = 0.877). The results indicate that cognitive-behavioral group counseling leads to positive changes in emotional management among high school students. Data analysis showed a significant difference between pre and post-intervention scores, with the average increasing from 80.57 to 101.14. The significance value was 0.001 (<0.05), supporting the conclusion that group counseling with a cognitive-behavioral approach is effective in fostering healthier and more adaptive emotional management in students.